Understanding the factors that influence cereal-legume adoption amongst smallholder farmers in Malawi - Nindi, Tabitha (International Food Policy Research Institute, 2021)
Although sustainable intensification (SI) practices such as intercropping of cereals with legumes are believed to offer productivity benefits to farmers, the adoption of cereal-legume intercropping remains low in Malawi. We use dynamic programing to assess the impact of four key constraints that smallholder farmers face. These constraints are i) land, ii) labor, ii) input market access and iv) output market access. We use the model to evaluate farmers’ optimal production plans across six scenarios in which these constraints are relaxed and compare their production plans across these scenarios. The farmer’s decision process given these alternative scenarios is modeled to assess the impact of these constraints on SI adoption decisions. Our model preliminary results suggest that both resource (land and labor) and institutional constraints (access to input and output market) play a key role in influencing smallholder farmers’ SI adoption decisions. The model results help to illustrate how labor constraints, land constraints and limited access to input and output market affect smallholders’ adoption of cereal-legume intercropping in Malawi.